2009
DOI: 10.1119/1.3160671
|View full text |Cite|
|
Sign up to set email alerts
|

Einstein on mass and energy

Abstract: This paper explores the evolution of Einstein's understanding of mass and energy. Early on, Einstein embraced the idea of a speed-dependent mass but changed his mind in 1906 and thereafter carefully avoided that notion entirely. He shunned, and explicitly rejected, what later came to be known as "relativistic mass." Nonetheless many textbooks and articles credit him with the relation E = mc 2 , where E is the total energy, m is the relativistic mass, and c is the vacuum speed of light. Einstein never derived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…It is seen in some sources (Born, 1962;Feynman, 1997) that mass varied depending on velocity based on the experimental validation of the predictions of special relativity. In recent years, it has been indicated that the concept of velocity-dependent mass was a misunderstanding and this fact had to be changed in all books and curricula (Hecht, 2009;Okun, 1989). Some books featuring special relativity changed the parts about the concept of "relative mass" in later editions (Serway & Beichner, 2000;Ünlü et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is seen in some sources (Born, 1962;Feynman, 1997) that mass varied depending on velocity based on the experimental validation of the predictions of special relativity. In recent years, it has been indicated that the concept of velocity-dependent mass was a misunderstanding and this fact had to be changed in all books and curricula (Hecht, 2009;Okun, 1989). Some books featuring special relativity changed the parts about the concept of "relative mass" in later editions (Serway & Beichner, 2000;Ünlü et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Let us make two final remarks. Contrary to popular belief, it seems Einstein himself never used E = mc 2 in the context of the equivalence of energy and mass -only E 0 = mc 2 , that is, equivalence of the rest energy and the invariant mass [3,51,52]. It may seem tempting to use this fact as evidence against velocity-dependent relativistic mass.…”
Section: Mass and Quantum Theorymentioning
confidence: 96%
“…While Einstein omitted a key feature of the formal derivation of the principle, his alternative argument stresses the notion that inert mass can be seen as latent energy, an idea that he regarded as the most important consequence of special relativity (Hecht, 2009). The rhetoric indeed seems epideictic, or status-driven (Fahnestock, 1986), particularly in comparison to the forensic style of the formal argument.…”
Section: The Rhetoricmentioning
confidence: 99%